Perencanaan SDM Strategis dalam Menghadapi Tantangan Otomatisasi Pekerjaan dan Adaptasi Keterampilan di Era Digital : Studi literasi - Nadila Maulida Mahmud; Nazwa Amanda Az'zahra; Fitria Nur Nilamsari; Alliyah Puteri Selyndra; Mada Aditia Wardhana (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2026)
The Fourth Industrial Revolution, digital transformation, and globalization have created a highly dynamic and competitive business environment, requiring organizations to adapt significantly. In this context, Human Resource Management (HRM) is considered a strategic asset to achieve competitive advantage and organizational sustainability. This study aims to analyze and develop innovative and effective HRM strategies to support digital transformation, enhance organizational performance and productivity, and address the challenges of job automation and disruption toward Society 5.0. Furthermore, the research highlights the role of Sustainable HRM in integrating the Triple Bottom Line (People, Planet, Profit) to strengthen corporate capabilities. Using a systematic literature review approach, this study emphasizes the importance of strategic workforce planning, continuous reskilling and upskilling, adoption of digital technologies, and fostering a growth mindset to ensure organizational resilience in the digital era. The findings suggest that innovative HRM strategies are essential for optimizing human capital and achieving long-term organizational success.